HASIL BELAJAR PEMROGRAMAN CNC DITINJAU DARI PERSEPSI TENTANG DUNIA KERJA DAN MINAT BELAJAR - Nofrizal Nofrizal; Wakito Waskito; Yuliana Yuliana (PAKAR Pendidikan, 2014)
This study aimed to analyze the relation (1) perception of the world of work with the learning outcomes CNC programming, (2) Interest in learning with learning outcomes of CNC programming Mechanical Engineering FT UNP in 2011, (3) perceptions about the world of work and interest in learning together with the learning outcomes of CNC programming Mechanical Engineering FT UNP in 2011. This study used a correlational. The sample in this research were 124 students from the Department of Mechanical Engineering FT UNP, used Slovin formula with proportional random sampling technique. The results showed (1) the value of correlation coefficient between the perception of the world of work with learning outcomes of CNC programming was of 0.438 with a medium correlation criteria, (2) the value of the correlation coefficient between interest in learning with learning outcomes of CNC programming was of 0.492 with medium correlation criteria, (3) value of the correlation coefficient between the perception of the world of work and interest in learning together with the results of student learning CNC programming FT UNP Department of Mechanical Engineering in 2011 at 0.557 with a medium correlation criteria.